The Reality of Teaching the France Language to non – Specialists at Tishreen University from the point of view of its Students - زريقي هيام صديق (Latakia University Journal - Arts and Humanities Sciences Series, 2021)
The purports of the research was to study the reality of teaching the France Language to non – Specialists at Tishreen University from the point of view of its students, and to study the different of such opinions according to variables (sex, and the year of study, Faculty), The study used the descriptive analytical approach, The sample included (306) students at Tishreen University for the academic year 2019/2020. To achieve the objectives of the study, questionnaire has been consisted of (38) statements distributed into four sections (services and facilities at Faculty, role of curriculum in teaching the France Language, role of student in teaching the France Language, role of Teacher in teaching the France Language). Validity of the questionnaire was established though a jury of (7) of the teaching staff of educational at Tishreen University. Pilot sample consisted of (22) students, Reliability was established through Cronbach – Alpha (0.899), which indicate to high Reliability to questionnaire. The final results showed that the reality of teaching the France Language to non – Specialists at Tishreen University was middle degree from the point of view of its students. In fact there are no found differences from the view point of the of sample study about the reality of teaching the France Language to non – Specialists at Tishreen University from the point of view of its students according to the variable (sex), but there are found differences in the degree it’s according to the variable (study year), in favour of third year, also to the variable (Faculty) in favour of scientific faculties. The study made many recommendations, the most important of which is preparing the infrastructure for colleges at University with modern technologies, and interesting with Teaching the France Language, and holding training courses at center Language at University.